PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PROSTITUSI SECARA ONLINE DIWILAYAH KOTA DUMAI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The existing regulations in Indonesia should have been able to curb the practice of prostitution through this virtual world. However, unfortunately, with the constraints of the existing limitations, the government has not been able to close down virtual world sites that clearly reek of the practice of prostitution.Based on the above understanding, the authors formulated three problem formulations, namely; First, how is the law enforcement of online prostitution in the city of Dumai. Second, what are the obstacles in enforcing the law of online prostitution in the City of Dumai. Third, what are the efforts to overcome obstacles in the enforcement of the law on online prostitution in the City of Dumai. This research is a sociological or empirical research, which is a type of research that uses people's assumptions in finding facts that occur in the field to answer an existing problem. This research was conducted in the jurisdiction of the Dumai City Police. While the population and sample are parties related to the problems studied in this study, the data sources used are primary data, secondary data, and tertiary data. Data collection techniques in this study are interviews and literature review.From the results of the study, there are three main problems that can be concluded, namely: First, law enforcement against online prostitution in the City of Dumai has not been optimal and the surrounding community does not care about the existence of online prostitution. Second, the problem faced by law enforcers is the lack of facilities and infrastructure for the Dumai City Police in conducting investigations and investigations. Third, the efforts made by law enforcers to overcome obstacles in the enforcement of online prostitution crimes in the Dumai City area are by taking preventive, preventive actions, namely preventive measures taken before the occurrence of a criminal event in terms of overcoming the crime of prostitution online by providing socialization to the community.Keywords: Law enforcement -Criminal act-Prostitution-Online-Dumai